Developing a coastal analysis system: the Guyana coastal analysis system (G-CAS) as an example for small island developing states (SIDS) - Oyedotun, Temitope D. Timothy; Poortinga, Ate; Tenneson, Karis; Wafiq, M. Warizmi; Suaruang, Weraphong; Nicolau, Andréa Puzzi; Hamer, Esan A.; Nedd, Gordon A.; Burningham, Helene (Frontiers in Environmental Science, 2025)
Small Island Developing States (SIDS) face significant challenges due to coastal hazards, climate change impacts, and data limitations that hinder effective coastal management. The Guyana Coastal Analysis System (G-CAS) was developed as a web-based geospatial tool to address these challenges by integrating remote sensing, machine learning, and cloud computing technologies. This study presents G-CAS as a replicable framework that enhances coastal monitoring and decision-making processes in Guyana and similar SIDS. The system consists of four core analytical modules: Shoreline Analysis, Coastal Squeeze Assessment, Bathymetric Change Detection, and Flood Detection and Modelling. These modules provide near real-time, data-driven insights into shoreline erosion, wetland compression, underwater depth variations, and flood risk exposure. Results from the application of the Shoreline Analysis module indicate spatially variable shoreline retreat rates, with critically eroded sections requiring urgent intervention. The Coastal Squeeze Assessment highlights areas where infrastructure restricts landward migration, increasing vulnerability to habitat loss. Bathymetric mapping reveals dynamic sediment transport patterns, essential for understanding coastal stability and marine ecosystem health. The Flood Detection and Modelling module assists in identifying high-risk zones, particularly in low-lying coastal settlements, supporting early warning systems and disaster mitigation planning. The offering of a cost-effective, scalable, and accessible coastal monitoring tool like G-CAS provides a data-driven foundation for coastal adaptation strategies in Guyana and beyond. The findings show the importance of integrating geospatial technologies into national coastal management frameworks to support climate resilience, disaster risk reduction, and sustainable development. This study highlights the potential for similar coastal analysis systems to be adopted across SIDS, ensuring evidence-based decision-making and enhanced environmental stewardship in response to climate change.